Non-target effect of herbicide mixtures on the mycelial growth of Rhizoctonia solani Kuhn - Raj, Sheeja K.; Syriac, Elizabeth K.; Geetha, D. (Journal of Tropical Agriculture, 2018)
Laboratory studies were carried out at Department of Plant Pathology, College of Agriculture,Vellayani to find out the in vitro effect of two new post emergence herbicide mixtures viz., bispyribac sodium + metamifop 14% SE and penoxsulam + cyhalofop butyl 6% OD on the mycelial growth of soil borne pathogen, Rhizoctonia solani causing sheath blight disease in rice. Results revealed that, as the concentration of herbicide mixtures increased a decrease in mycelial growth and an increase in percentage growth inhibition was observed. The lowest concentration of bispyribac sodium + metamifop (100 μl l-1) recorded a colony diameter of 5.27 cm and highest concentration (220 μl l-1) recorded a colony diameter of 0.47 cm with a percentage growth inhibition of 41.48 and 94.81 respectively. Similarly, the lowest concentration of penoxsulam + cyhalofop butyl (230 μl l-1) recorded a mycelial growth of 7.87 cm and the highest concentration recorded a mycelial growth of 0.83 cm diameter with a growth inhibition of 12.61 and 90.74 per cent, respectively. The results indicated that both the herbicide mixtures have immense suppressive effect on the growth of Rhizoctonia solani. The inhibitory effect of bispyribac sodium + metamifop 14% SE and penoxsulam + cyhalofop butyl 6% OD on the growth of Rhizoctonia solani can be successfully utilized in integrated pest and disease management programme.